PENGARUH CELEBRITY ENDORSER, BRAND ASSOCIATION, BRAND PERSONALITY DAN PRODUCT CHARACTERISTICS DALAM MENCIPTAKAN INTENSI PEMBELIAN (Studi pada Iklan Kuku Bima Ener-G Rosa Versi Chris John) - Nurani, Eka Setya; Haryanto, Jony Oktavian (Bina Nusantara University, 2010)
This study is aimed to determine how the influence of celebrity endorser, brand association, brand personality and product characteristics in created the intention to buy energy drinks Kuku Bima Ener-G Rosa. This study is took the 200 respondents and used judgmental sampling method. Data analysis techniques used factor analysis and multiple regression analysis. The results showed that the brand association and product characteristic significantly influence the intention to buy Kuku Bima Ener-G Rosa, while the celebrity endorser and the brand personality does not significantly influence the intention to buy Kuku Bima Ener-G Rosa. Thus, PT. Sido Muncul should use the popular commercials that have power and physical attraction or personality so can influence the consumer, and more attention to the formation of a clear brand personality and strong product, because will be consumer in buying product which according to him.